2014
DOI: 10.3961/jpmph.2014.47.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting the Physical Activity Behavior of Female Adolescents: A Test of the Health Promotion Model

Abstract: ObjectivesPhysical activity behavior begins to decline during adolescence and continues to decrease throughout young adulthood. This study aims to explain factors that influence physical activity behavior in a sample of female adolescents using a health promotion model framework.MethodsThis cross-sectional survey was used to explore physical activity behavior among a sample of female adolescents. Participants completed measures of physical activity, perceived self-efficacy, self-esteem, social support, perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…The positive, direct effect of PA self‐efficacy on MVPA is consistent with other studies that tested the HPM among adolescents (Bajamal et al, ; Mohamadian & Arani, ; Taymoori, Lubans et al, ; Taymoori, Rhodes, & Berry, ; Wu & Pender, ; Wu & Pender, ; Wu et al, ). While these studies have reported effects (β = .21–.61) that support self‐efficacy as a predictor of self‐reported PA, none reported CIs and only one reported a standard error (Bajamal et al, ) making it difficult to determine the magnitude of the effects across studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The positive, direct effect of PA self‐efficacy on MVPA is consistent with other studies that tested the HPM among adolescents (Bajamal et al, ; Mohamadian & Arani, ; Taymoori, Lubans et al, ; Taymoori, Rhodes, & Berry, ; Wu & Pender, ; Wu & Pender, ; Wu et al, ). While these studies have reported effects (β = .21–.61) that support self‐efficacy as a predictor of self‐reported PA, none reported CIs and only one reported a standard error (Bajamal et al, ) making it difficult to determine the magnitude of the effects across studies.…”
Section: Discussionsupporting
confidence: 86%
“…The HPM has been tested specifically with PA as a health‐promoting behavior among adolescents in several studies (Ammouri, Kaur, Neuberger, Gajewski, & Choi, ; Bajamal et al, ; Garcia et al, ; Mohamadian & Arani, ; Taymoori, Lubans, & Berry, ; Wu & Pender, ; Wu & Pender, ; Wu, Pender, & Noureddine, ). In these studies, all of which included self‐reported PA, self‐efficacy has emerged as the most consistent predictor of PA.…”
Section: Introductionmentioning
confidence: 99%
“…achievement, success, and satisfaction) (Mann, Hosman, Schaalma, & de Vries, 2004). According to previous empirical researches, it has been established that self-esteem influences human health behaviors (Hoare & Cosgrove, 1998;Mohamadian & Arani, 2014;Park, Schepp, Jang, & Koo, 2006;Tomori & Rus-Makovec, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activities prevent or control obesity and improve health conditions [3]. Diet is also considered essential for preventing and controlling obesity [4].…”
Section: The Necessity Of Researchmentioning
confidence: 99%